2010
DOI: 10.1038/onc.2010.292
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular adenosine triphosphate and adenosine in cancer

Abstract: Adenosine triphosphate (ATP) is actively released in the extracellular environment in response to tissue damage and cellular stress. Through the activation of P2X and P2Y receptors, extracellular ATP enhances tissue repair, promotes the recruitment of immune phagocytes and dendritic cells, and acts as a co-activator of NLR family, pyrin domain-containing 3 (NLRP3) inflammasomes. The conversion of extracellular ATP to adenosine, in contrast, essentially through the enzymatic activity of the ecto-nucleotidases C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
458
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 503 publications
(480 citation statements)
references
References 145 publications
5
458
0
7
Order By: Relevance
“…In addition, ATP and adenosine participates in inflammatory signaling [43]. ATP has been described as a pro-inflammatory molecule acting as a chemotactic signal to immune phagocytes [44,45] while adenosine has an immunosuppressive role Fig. 4 a The images correspond to immunofluorescent staining of ecto-5′-NT/CD73 in different times of bladder cancer induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ATP and adenosine participates in inflammatory signaling [43]. ATP has been described as a pro-inflammatory molecule acting as a chemotactic signal to immune phagocytes [44,45] while adenosine has an immunosuppressive role Fig. 4 a The images correspond to immunofluorescent staining of ecto-5′-NT/CD73 in different times of bladder cancer induction.…”
Section: Discussionmentioning
confidence: 99%
“…* Significantly different compared to control. # Significantly different to all other groups suppressing innate and adaptative immune responses [44]. The participation of altered ectonucleotidases expression in the modulation of immune cells to contribute to cancer progress have been described to gliomas [46], that have a similar ATP/ADP/AMPase activity pattern of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, altered expression of CD73 and other molecules that regulate the nucleotide environment of cancer cells may contribute to metastasis and an overall insidious cell phenotype that allows invasion of the extracellular matrix and the spread of tumors to other organs. This may explain the findings by Stagg et al who reported that CD73 expression contributes to in vitro cancer cell migration in a transwell chamber model and to tumor growth and metastasis in vivo [44,45]. However, the tumor-enhancing pro-migratory and prometastatic properties of CD73 are controversial.…”
Section: Discussionmentioning
confidence: 91%
“…2). The tumor microenvironment is rich in extracellular ATP [44,45]. Depending on the ectonucleotidases present, high levels of extracellular ATP and its breakdown proct adenosine could entrap cancer cells within the tumor environment or promote random motility and the spread of cancer cells outside of tumors.…”
Section: Discussionmentioning
confidence: 99%